Fulminant Diabetes in the Context Of COVID-19 Pandemic: The Resurgence of Pancreatic Insulitis? - A, Soghomonian; C, Vincentelli; A, Jacquier; M, Di Bisceglie; K, Chaumoitre; P, Ancel; D, Taieb; N, Sahakhian; O, Ronsin; S, Boullu; et al. (Archives of Clinical and Biomedical Research, 2020)
Abstract not available in the source database.